2019
DOI: 10.1093/jnci/djz212
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Precision Medicine on Efficiencies of Novel Drug Development in Cancer

Abstract: Precision medicine (PM) offers opportunities for reducing the costs, burdens, and time associated with drug development. We examined time, number of trials, indications tested, and patient burden needed to achieve first U.S. Food and Drug Administration license for all five novel anticancer PM drugs and all 10 novel non-PM drugs receiving U.S. Food and Drug Administration approval during 2010–2014. The 15 drug portfolios encompassed 242 trials: 87 for PM drugs and 155 for non-PM drugs. Embase and MEDLINE datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…It differs from prior studies that confined their assessment to successful drug development efforts. 7 , 8 We estimated that 12 217 patients were required to advance a new oncology drug from initial test of efficacy to regulatory licensure. However, many drugs that gain licensure have limited clinical impact.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It differs from prior studies that confined their assessment to successful drug development efforts. 7 , 8 We estimated that 12 217 patients were required to advance a new oncology drug from initial test of efficacy to regulatory licensure. However, many drugs that gain licensure have limited clinical impact.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of patient enrollment have shown that a median of 1708 patients participated in clinical trials per European Medicines Agency new molecular entity approval 7 ; a median of 2316 patients were studied per US Food and Drug Administration (FDA) approval of a precision medicine oncology drug. 8 However, these studies restricted their analyses to approved drugs and thus do not account for the large numbers of patients participating in unsuccessful drug development efforts. Estimates that include all patient study participants can make more visible the degree to which private drug development efforts build on public volunteerism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer treatment costs account for a substantial part of health care expenditure [1]. The costs have increased due to advancements in novel drugs and therapy innovations, such as genomic testing, in the last decade [2]. It is difficult to compare results from different countries directly as the absolute cost of cancer treatment is influenced by each country's socioeconomic environment, health care system and income level [3].…”
Section: Introductionmentioning
confidence: 99%